Colon Fistula: A Conditioning Treatment - Cordero, Carlos Alberto Martínez; Guzmán, Elsa Nalleli Romero; Castillo, Max Cristopher Rodriguez; Miranda, Katia Berenice Pineda; Ramírez, Adolfo García; Acevedo, Samuel Abraham Gómez; Valiente, Mariana González; Solórzano, Dan Jeerebai Castro; Vargas, Astrid Ortiz; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2025)
Introduction: colon or rectal fistula is a medical/surgical challenge that, with precedents and resilience, is presented as a complication of another real cause and fistula is defined as the path in abnormal communication between one epithelium and another. Objective: to present the experience of seven years in diagnosis and treatment in four hospitals in Mexico City. Method: this is a study with a multicenter, retrospective, longitudinal, observational and descriptive design. In the Colon and Rectal Surgery services, as well as General Surgery of the second and third level of health care. Results: from 118 records, a total of 46 patients with colon fistula were chosen, of which 17 were male (36.95 %) and 29 were female (63.04 %). With an age range of 21 to 82 years, with an average of 61 years and a bimodal value of 33 and 64 years. Its etiology was diverse, but its presentation was documented as entero-cutaneous, entero-bladder, entero-vaginal, entero-uterine, entero-enteric fistulas. Discussion: the diagnosis of colon fistula is made with a complete medical history, which is mostly clinically evident with the classic triad. The gold standard for confirming a diagnosis of acute diverticulitis and evaluating complications is CT scan with contrast of the abdomen; the treatment alternatives for colon fistulas to another organ varies according to the case, the clinical conditions and/or their prognosis of cure according to the Chapman and Sheldon stages; successful conservative management or treatment in hemodynamically stable patients, offering less invasive alternatives in selected clinical scenarios, or even fecal transplants in patients with complicated diverticulitis; however, surgical intervention remains the definitive treatment for symptomatic or complicated fistulas. Conclusions: regarding the treatment of colon fistulas, this will be conditioned according to each patient, by the hemodynamic conditions, the etiology, the characteristics of nutrition/infection and of course the surgeon's expertise, as well as the infrastructure of the installed capacity that is available.